New Perspectives on Surface Passivation: Understanding the Si-Al2O3 Interface - Black, Lachlan E. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
The book addresses the problem of passivation at the surface of crystalline silicon solar cells. More specifically, it reports on a high-throughput, industrially compatible deposition method for Al2O3, enabling its application to commercial solar cells. One of the main focus is on the analysis of the physics of Al2O3 as a passivating dielectric for silicon surfaces. This is accomplished through a comprehensive study, which moves from the particular, the case of aluminium oxide on silicon, to the general, the physics of surface recombination, and is able to connect theory with practice, highlighting relevant commercial applications.